A biophysical observation of Mahakam River around Tanjung Una of Kutai Kartanegara, Indonesia - IWAN SUYATNA; MISLAN MISLAN; ANDRY RAHMAN; ARY WINATA; YUNI IRAWATI WIJAYA (Society for Indonesian Biodiversity, 2017)
Suyatna, I, Mislan. A. Rahman A. Winta Wijaya YI. 2017. A biophysical observation of Mahakam River around Tanjung Una of Kutai Kartanegara, Indonesia. Biodiversitas 18: 623-632. The aim of this study is to dig up more information about the biophysical conditions of Mahakam River around Tanjung Una of Kutai Kartanegara, Indonesia including the fishery potential in these locations. The observations were conducted in two periods. Through field surveys, the sample of fish and shrimp were caught with pulled nets from many stations, while to know the water quality around the location of the observation, water sampling was conducted and then the sample was brought to a laboratory to be analyzed in order to find out its quality. On the scale of taxonomy and ecology, community structure of fish and shrimp from 21 species of fish consisted of 17 families, five orders, and one class. For the shrimp, it was only four identified species of the genus Macrobrachium family Palaemonidae and genus Metapenaeus family Penaeidae ordo Decapoda class Malacostraca. The distribution of the length and weight of fish and shrimp was found out to be small. The value of the diversity index between the fish and shrimp showed low to moderate with a value of D: 0.150 to 0.601; H': from 0.986 to 2.089, E: 0.268 to 0.621 and Margalef: 1,475-2,345 for the fish and a value of D: 0.325 to 0.688, H': from 0.615 to 1.205, E: 0.462 to 0.834 and Margalef: from 0.490 to 0.614 for the shrimp. The index indicated that there were species that tend to dominate other species. The species richness was low. Physical-chemical properties and heavy metal content in the Mahakam River around Tanjung Una were generally still below the quality standard. The observations concluded that the number of marine fish species was found two times higher than the river fish species, but not to the number of population.